Small scale bio-LNG plant: Comparison of different biogas upgrading techniques. (1st May 2018) - Baccioli, A.; Antonelli, M.; Frigo, S.; Desideri, U.; Pasini, G.
Highlights: Small size liquefaction plants for biogas are studied. Different biogas upgrading techniques are studied. Liquefaction energy consumption can be as low as 0.61 kWh/Stm3 of raw biogas processed. Liquefaction with liquid nitrogen is the best option. Abstract: In this paper, a comparison of two different small bio-LNG plants for upgrading and liquefaction have been conducted. In the first configuration liquefaction of the biomethane occurred after the upgrading with conventional processes; in the second configuration, cryogenic upgrading occurred within the liquefaction process, removing CO2 in solid state. For both the two configurations, a two-pressure levels Joule-Brayton reverse cycle, with nitrogen as working fluid, has been considered as refrigeration cycle. The two systems have been simulated and optimized in ASPEN HYSYS, determining the values of the various working parameters which minimized the energy specific consumption. Results showed that a bio-LNG plant with cryogenic upgrading did not require any pre-treatment of raw biogas and reached a very promising energy consumption: 0.61 kWh/Stm 3 of raw biogas processed, equivalent to 1.45 kWh/kg of bio-LNG produced. Bio-LNG plants with standard upgrading techniques required between 0.57 and 0.72 kWh/Stm 3 without considering additions for heating and raw biogas pre-treatment. A sensitivity analysis concerning CH4 content in bio-LNG and intercooling temperature has been accomplished for bio-LNG plants with cryogenic upgrading, proving their impact in specific energy consumption. A standalone bio-LNG plant cryogenic upgrading, with a natural gas internal combustion engine for energy supply, has been studied and briefly discussed. Some solutions for waste heat utilization have been proposed (digesters warming, energy recovery).